Nanoengineered Advanced Materials for Enabling Hydrogen Economy: Functionalized Graphene–Incorporated Cupric Oxide Catalyst for Efficient Solar Hydrogen Production. Issue 3 (24th January 2020) - Dalapati, Goutam Kumar; Masudy‐Panah, Saeid; Moakhar, Roozbeh Siavash; Chakrabortty, Sabyasachi; Ghosh, Siddhartha; Kushwaha, Ajay; Katal, Reza; Chua, Chin Sheng; Xiao, Gong; Tripathy, Sudhiranjan; Ramakrishna, Seeram
Abstract: Cupric oxide (CuO) is a promising candidate as a photocathode for visible‐light‐driven photo‐electrochemical (PEC) water splitting. However, the stability of the CuO photocathode against photo‐corrosion is crucial for developing CuO‐based PEC cells. This study demonstrates a stable and efficient photocathode through the introduction of graphene into CuO film (CuO:G). The CuO:G composite electrodes are prepared using graphene‐incorporated CuO sol–gel solution via spin‐coating techniques. The graphene is modified with two different types of functional groups, such as amine (NH2 ) and carboxylic acid (COOH). The COOH‐functionalized graphene incorporation into CuO photocathode exhibits better stability and also improves the photocurrent generation compare to control CuO electrode. In addition, COOH‐functionalized graphene reduces the conversion of CuO phase into cuprous oxide (Cu2 O) during photo‐electrochemical reaction due to effective charge transfer and leads to a more stable photocathode. The reduction of CuO to Cu2 O phase is significantly lesser in CuO:G‐COOH as compared to CuO and CuO:G‐NH2 photocathodes. The photocatalytic degradation of methylene blue (MB) by CuO, CuO:G‐NH2 and CuO:G‐COOH is also investigated. By integrating CuO:G‐COOH photocathode with a sol–gel‐deposited TiO2 protecting layer and Au–Pd nanostructure, stable and efficient photocathode are developed for solar hydrogen generation. Abstract : Graphene‐incorporated cupric oxide (CuO:G) is a stable and efficient photocathode. The CuO:G electrodes are prepared using sol–gel solution via spin‐coating. The –COOH‐functionalized graphene reduces CuO phase conversion into cuprous oxide (Cu2 O) during photo‐electrochemical reaction and leads to a more stable photocathode for solar hydrogen generation. The CuO:G electrodes are also efficient for the dye degradation.